Where ‘the unbelievable and the obvious collide’: Spiritual practices and everyday life - Marchinkowski, George (Verbum et ecclesia, 2022)
Responding to the discernment that the Christian faith may need to pivot towards a more monastic or even mystical frame so as to offer an invitation to the ‘spiritual-but-not-religious’, this article offers spiritual practices as a bridge. After exploring what a spiritual practice is and examining some characteristics of spiritual practices to show how dynamic they are, this article will investigate the relationship between beliefs and practices. Then, it will examine the work of Michel de Certeau and David Steindl-Rast to make an argument for practices belonging to ordinary people and everyday life. Finally, this article will offer the work of the contemporary author Barbara Brown Taylor and her understanding of practices as everyday tasks to show how a turn to the monastic and mystical is in fact a viable prospect. Intradisciplinary and/or interdisciplinary implications: This article contributes to scholarship on spiritual practices by examining their characteristics and usefulness for people who are alienated from the institutional church yet seeking connection with the Divine. It does so by placing practices in the context of everyday life and in the domain of ordinary people.